2003
DOI: 10.1152/ajplung.00494.2001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of NO on carotid body: contribution of neural and endothelial nitric oxide synthase isoforms

Abstract: Valdé s, Viviana, Matías Mosqueira, Sergio Rey, Rodrigo Del Rio, and Rodrigo Iturriaga. Inhibitory effects of NO on carotid body: contribution of neural and endothelial nitric oxide synthase isoforms. Am J Physiol Lung Cell Mol Physiol 284: L57-L68, 2003. First published September 6, 2002 10.1152/ajplung.00494.2001.-We tested the hypothesis that nitric oxide (NO) produced within the carotid body is a tonic inhibitor of chemoreception and determined the contribution of neuronal and endothelial nitric oxide sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 39 publications
1
18
0
1
Order By: Relevance
“…Existing evidence of the role of eNOS vs nNOS in the CB is somewhat controversial. Studies have shown that a nonspecific NOS inhibitor,N G -nitro-L-arginine methyl ester (L-NAME), significantly enhances the CB ventilatory response in rats (Haxhiu et al 1995) and cats (Valdés et al 2003); but specific nNOS inhibitors were ineffective. On the other hand, using mutant mice deficient in nNOS and eNOS isoforms, (Kline et al 1998) found that mice lacking nNOS showed greater ventilatory responses to hypoxia than wild-type controls; whereas responses to hypoxia were blunted in mutant mice lacking eNOS compared with the wild-type.…”
Section: Role Of No On Cb Function In Chfmentioning
confidence: 99%
“…Existing evidence of the role of eNOS vs nNOS in the CB is somewhat controversial. Studies have shown that a nonspecific NOS inhibitor,N G -nitro-L-arginine methyl ester (L-NAME), significantly enhances the CB ventilatory response in rats (Haxhiu et al 1995) and cats (Valdés et al 2003); but specific nNOS inhibitors were ineffective. On the other hand, using mutant mice deficient in nNOS and eNOS isoforms, (Kline et al 1998) found that mice lacking nNOS showed greater ventilatory responses to hypoxia than wild-type controls; whereas responses to hypoxia were blunted in mutant mice lacking eNOS compared with the wild-type.…”
Section: Role Of No On Cb Function In Chfmentioning
confidence: 99%
“…Several studies have shown that a nonspecific NOS inhibitor, L-NAME, significantly enhances the ventilatory response to NaCN in rats 3 and CB response to hypoxia in cats; 23 but specific nNOS inhibitors were ineffective on them. 3,23 Conversely, using mutant mice deficient in nNOS and eNOS isoforms, Kline et al 24,25 found that mice lacking nNOS showed greater ventilatory responses to hypoxia than wild-type controls; whereas responses to hypoxia were blunted in mutant mice lacking eNOS compared with the wild-type.Our study confirms previous studies showing the presence of nNOS in nerve fibers in the CB. 5,22 Furthermore, our results demonstrate that nNOS protein expression and NO production are markedly lower in the CB from CHF rabbits compared with that in sham rabbits.…”
mentioning
confidence: 99%
“…Two studies concluded that a nonspecific NOS inhibitor, L-NAME, significantly enhanced the ventilatory response to NaCN in rat 3 and the CB chemoreceptor response to hypoxia in cats; 23 whereas specific nNOS inhibitors were ineffective. 3,23 Conversely, Kline et al, 24,25 using mutant mice deficient in nNOS and eNOS isoforms, found that mice lacking nNOS showed greater ventilatory responses to hypoxia than wild-type controls; whereas responses to hypoxia were blunted in mutant mice lacking eNOS compared with the wild-type. Until now, even less is known about which isoform of NOS contributes to the enhanced peripheral chemoreceptor activity in CHF rabbits.…”
mentioning
confidence: 99%
“…Studies have shown the expression of purinoceptor subunits P2X2 and P2X3 in the nerve fibers co-localized with the glomus clusters [15,31]. In addition, NOS is localized in the nerve endings and plexus of nerve fibers in lobules of parenchyma cells and near small blood vessels of the carotid body, which plays physiological role in the NO inhibition of carotid chemoreceptor activity [25,26,32,33].…”
Section: Discussionmentioning
confidence: 99%